Profile and predictors of health related quality-of-life in a hypertensive population of Pakistan - Fahad Saleem; Mohamed Azmi Hassali; Asrul Akmal Shafie; Noman Ul Haq; Maryam Farooqui; Hisham Aljadhey (Archives of Global Professionals, 2013)
Objectives: This study aims to describe the profile and predictors of health related quality-of-life (HRQoL) in a hypertensive population of Pakistan. Materials and Methods: A questionnaire based, cross-sectional study was conducted among 385 hypertensive patients visiting two public hospitals in the city of Quetta, Pakistan. Demographic and disease related data was obtained from patients and their hospital records. Euroqol quality-of-life questionnaire was used to measure HRQoL while drug attitude inventory and hypertension fact questionnaire were used to measure medication adherence and HTN related knowledge respectively. Scale scores were compared with Mann-Whitney and Kruskal-Wallis test. Standard multiple regression analysis was used to identify predictors of HRQoL. Results: Patients in the current study reported poor HRQoL with a mean score of 0.46 ± 0.28. In terms of practical implementation, age (é =0.298, P < 0.001), educational level (ß =0.493, P = 0.025) and knowledge score (ß =0.351, P = 0.024) reached level of significance in the multivariate analysis. The multiple regression analysis also found that variables such as gender, occupation, income, locality, duration of disease and medication adherence were not significantly associated with HRQoL. Conclusion: The results of the present study provide an evidence for a model that correlates with patients' socio-demographic information and HRQoL. The findings after implication in clinical practice can prove useful in guiding patients receiving treatment for HTN. It will also help the physicians to maintain and adjust treatment behaviors with drug or non-drug related interventions.